2009
DOI: 10.1159/000267850
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Peripheral Arterial Disease in Patients with Acute Ischaemic Stroke

Abstract: Background: After acute ischaemic stroke (AIS) or transient ischaemic attack (TIA), the detection of peripheral arterial disease (PAD) as a marker of generalized atherosclerosis may improve the risk stratification and prevention of future atherothrombotic events. We aimed to determine the prevalence of PAD indicated by an ankle-brachial index (ABI) of ≤0.9 in a large cohort of patients with AIS/TIA. Methods: In this prospective, multicentre, Austrian, cross-sectional study (OECROSS), 759 patients with AIS or T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 55 publications
2
29
0
1
Order By: Relevance
“…In addition, several studies have reported that the CHADS2 score can be used to predict subsequent cardiovascular events and new-onset AF in non-AF populations [11][12][13] . As an older age, hypertension, diabetes, congestive heart failure and stroke are all risk factors for PAOD [1][2][3][4][5][6][7] , our recent cross-sectional study demonstrated that the CHADS2 score is significantly associated with an ankle-brachial index (ABI) of 0.9 in non-AF patients 14) . However, divided the study patients into four groups: group 1 (score 0), group 2 (score 1-2), group 3 (score 3-4) and group 4 (score 5-6).…”
Section: Data Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several studies have reported that the CHADS2 score can be used to predict subsequent cardiovascular events and new-onset AF in non-AF populations [11][12][13] . As an older age, hypertension, diabetes, congestive heart failure and stroke are all risk factors for PAOD [1][2][3][4][5][6][7] , our recent cross-sectional study demonstrated that the CHADS2 score is significantly associated with an ankle-brachial index (ABI) of 0.9 in non-AF patients 14) . However, divided the study patients into four groups: group 1 (score 0), group 2 (score 1-2), group 3 (score 3-4) and group 4 (score 5-6).…”
Section: Data Sourcementioning
confidence: 99%
“…This condition shares similar risk factors with both coronary artery and cerebrovascular disease. Risk factors for PAOD include an advanced age, smoking, hypertension, diabetes, dyslipidemia, chronic kidney disease, congestive heart failure, stroke, race, obesity, elevated inflammatory markers and so on [1][2][3][4][5][6][7] . The CHADS2 score is a useful and well-known clinical score for assessing the risk of stroke in patients with AF 8,9) .…”
Section: Incidence Of Paod In Taiwanmentioning
confidence: 99%
See 1 more Smart Citation
“…В последние годы стали обращать внимание на тот факт, что оценка ЛПИ может иметь прогностическое значение в различных когортах обследованных [11], не только в эпидемиологических исследованиях, но и у па-циентов с наличием ССЗ [12]. Недавно опубликованы исследования по прогностическому значению ЛПИ у больных ОНМК [13], однако до сих пор такие иссле-дования проводили в зарубежных странах, отече-ственные исследования ЛПИ при ОНМК только стали появляться, и касаются только отдельных клинических вопросов данной тематики [14]. В российской практике лечения больных после ОНМК до сих пор сохраняет-ся проблема назначения оптимальной медикамен-тозной терапии [15], что сопровождается более высо-кой частотой ССО и смертностью после перенесенного инсульта [4].…”
Section: Annual Prognosis After Stroke: Role Of Ankle-brachial Index unclassified
“…PAOD is a systemic atherosclerotic process for whichthemajorriskfactorsaresimilartoatherosclerosisinthecoronaryandcarotidarteries 6) .Majorrisk factors for PAOD include an advanced age, cigarette smoking, diabetes mellitus, dyslipidemia and hypertension [6][7] . In addition, chronic kidney disease, race, obesity, elevated inflammatory markers, stroke and congestiveheartfailurehavealsobeenreportedtobe associatedwithPAOD [6][7][8][9][10][11][12] . The CHADS2 (congestive heart failure, hypertension,age≧75years,diabetes,priorstroke)scoreis a reliable, simple and popular clinical score that is usedtoassesstheriskofstrokeinpatientswithatrial surementwasperformedonceineachpatient.…”
Section: Introductionmentioning
confidence: 99%